Irigenin inhibits glioblastoma progression through suppressing YAP/β-catenin signaling - Jiayun Xu; Jiayun Xu; Shanshan Sun; Shanshan Sun; Wei Zhang; Wei Zhang; Jianhong Dong; Jianhong Dong; Changgang Huang; Changgang Huang; Xin Wang; Xin Wang; et al. (Frontiers Media S.A., 2022)
Glioblastoma (GBM) is the most malignant glioma in brain tumors with low survival and high recurrence rate. Irigenin, as an isoflavone compound extracted from Shegan, has shown many pharmacological functions such as antioxidant, anti-inflammatory and anti-tumor. However, the effects of irigenin on GBM cells and the related molecular mechanisms remain unexplored. In this study, we found that irigenin inhibited the proliferation of GBM cells in a dose-dependent manner by several assays in vitro. Subsequently, we found that irigenin arrested cell cycle at G2/M phase and induced apoptosis of GBM cells in vitro. In addition, irigenin inhibited the migration of GBM cells. Mechanically, we found that irigenin treatment decreased the expression of YAP (yes-associated protein), suppressed β-catenin signaling. Furthermore, overexpression of YAP partially restored the anti-tumor effects of irigenin on GBM cells in vitro. Finally, we found that irigenin inhibited the growth of tumor in GBM xenograft mice model through inactivation of YAP. Taken together, these results suggest that irigenin exerts its anticancer effects on GBM via inhibiting YAP/β-catenin signaling, which may provide a new strategy for the treatment of GBM.